REGIONAL COOPERATION ON THE BLACK SEA: ACHIEVEMENTS, PROBLEMS, PROSPECTS - E. D. Eshba (Vestnik MGIMO-Universiteta)
Throughout the history The Black Sea region attracted attention of both regional states and those lying far beyond its borders . One of the main reasons for increased attention to the Black Sea coast is its transit location : it is crossed by transport routes connecting the West with the states of Central Asia and Transcaucasia that are rich by hydrocarbon resources . A large-scale and fairly ambitious gas pipeline projects that are scheduled to take place on the territory of the Black Sea countries and across the Black Sea lead us to expect the increasing role of the Black Sea region in the world economic system. In this regard, the author brings to light the problem of the main stages of the development of cooperation among the Black Sea countries be means of analysis of the most successful attempts at regional cooperation. Special attention is paid to the policy of Turkey in the Black Sea and on the interactions of two major regional actors (Russia and Turkey) . In addition, the work highlights the most promising areas of transport, logistics , trade and economic development of the region , including the project of ring highway around the Black Sea, as well as prospects for the intensification of maritime transport and the development of new marine transportation routes. To summarize, the author concludes that , despite the development of cooperation in the region , there are problems in the formation of a comprehensive system of regional security and cooperation, so as major obstacles to the successful implementation of the plan of cooperation in the Black Sea region still remain .